Managing the Process of Creating the University's Student Ecosystem - Glushchenko Valery Vladimirovich (Indonesian Journal of Multidiciplinary Research, 2023)
The subject of the article is the methodological aspects of managing the process of creating the University's student ecosystem. The object of the article is the university's student ecosystem. the purpose of the work is to increase the efficiency of the process of creating the university's student ecosystem. To achieve this goal, the following tasks are solved: descriptions of the essence and content of the university's student ecosystem, the formation of a conceptual approach to designing the university's student ecosystem, the adaptation of the ergo design method in the interest of its use in the creation of the university's student ecosystem, discussion on the organizational culture of the university's student ecosystem, suggestion, and discussion on criteria for evaluating the effectiveness of the university's student ecosystem. This also studies the risks of creating a university's student ecosystem. Scientific methods in the article are ecosystem approach, historical analysis, system synthesis and analysis, methodology of ergonomic design, eco-system approach, and forecasting. The scientific novelty of the article is determined by the formation of methodological foundations for the creation of student systems at universities.